LINES TRACKERS ROBOT SENSOR INFRARED LINES THROUGH AT89C52 MICROCONTROLLER - Ari Wibowo susanto,; Drs. Lingga Hermanto, MMSI (Jurnal Sistem Komputer, 2006)
Autonomous Mobile Robot (AMR) is the robot that has the ability to move towards a certain point without human intervention. This research has built an AMR which has a mission to follow a line that has been determined by using infrared light as the sensor line. The purpose of this thesis is to design and implement a Line Tracer Robot using AT89C52 microcontroller and infrared sensors. AT89C52 microcontroller is used as the control center. Interruption of its facilities is very useful in responding to a line that is detected by sensors in real-time line.